12+1.5a = 3a
12 = 3a-1.5a
12 = 1.5a
Divide both sides by 1.5 to find the value of a:
a = 8
5
-3a-12 = 12+12 +12-3a = +12~ ~-3 -3a = -8
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
To factor the expression 15a - 25b + 20, we first look for common factors among the terms. The greatest common factor among the coefficients is 5. We can then factor out 5 to get 5(3a - 5b + 4). This is the factored form of the expression 15a - 25b + 20.
6 + 12 - 5 = 13
To factor the expression 15a - 25b + 20, we first look for common factors among the terms. The greatest common factor among the coefficients is 5. We can then factor out 5 to get 5(3a - 5b + 4). This is the factored form of the expression 15a - 25b + 20.
12
It is: 5(3a+b) when factored
5
5(3a - 5b + 4)
-3a-12 = 12+12 +12-3a = +12~ ~-3 -3a = -8
a(4a - 3)(3a - 5)
If a + b = 6, what is the value of 3a + 3b?
If: -3a+2 = 12 Then: a = -3 and 1/3
4a+3-a =12 4a-a = 12-3 3a = 9 a = 3
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
Yes. 3a plus 12 plus 6 is an example of an Equation.